Pengembangan Model Pembelajaran Berbasis Web untuk Pelajaran Matematika - -, Fadli (JTP - Jurnal Teknologi Pendidikan, 2014)
The research is aimed develop web-based intructional model of mathematics les- sons. Respondents are limited to students of class XI IPA MAN 3 Palembang.The method used is the Research and Development (R & D). To see the feasibility of the model devel- oped, the expert researcher conduct several tests, test 1-1, small group testing, and eld trials with indicators of how attitudes and student learning outcomes.The results showed the fourth prototype is potential effective design when used at the time of learning. It shown that 65.63% of students have interested attitude towards the developed model. In addition, students achieve mastery of learning outcome shown at 79.69%. It can be concluded that the model developed has been effective in increasing students interest in mathematics.